PENGARUH LAYANAN MOBILE BANKING TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA Tbk. KANTOR CABANG SAMBAS - Yola Mutia, Listy; Muslimin (Cross-Border Journal of Business Management, 2025)
In the era of globalization, the development of information technology has become an urgent need in various sectors, including banking. Bank Syariah Indonesia (BSI) provides mobile banking services aimed at facilitating banking transactions and increasing customer satisfaction. This study aims to analyze the influence of mobile banking services on customer satisfaction at the BSI Sambas Branch. The method used in this study is quantitative, with data collected through questionnaires distributed to 30 BSI mobile banking service users. Data were analyzed using IBM SPSS Statistics 26 to test validity, reliability, and perform a simple linear regression test. The study results show that BSI’s mobile banking services have a positive and significant influence on customer satisfaction, with a determination coefficient (R²) of 0.613, meaning that 61.3% of the variation in customer satisfaction is explained by the quality of mobile banking services. All questionnaire items are valid at the 5% significance level and reliable with a Cronbach's Alpha value greater than 0.6. The majority of respondents are female, aged 23-30 years, with a high school education, and work as entrepreneurs. These findings recommend that BSI enhance the aspects of security, ease of use, privacy, reliability, credibility, and system speed in its mobile banking services. These improvements are expected to increase customer satisfaction and loyalty toward BSI’s digital services